How do you simplify 2√3 + √2 - 4√3?

1 Answer
Sep 24, 2015

Answer:

#color(red)(2sqrt3 + sqrt2-4sqrt 3 = sqrt2 – 2sqrt3)#

Explanation:

#2sqrt3 + sqrt2-4sqrt 3#

Start by combining the #sqrt3# terms.

#2sqrt3 + sqrt2 - 4sqrt 3 = sqrt2 + 2sqrt3 -4sqrt3#

Factor #sqrt3# from the last two terms.

#sqrt2 + 2sqrt3 -4sqrt3 = sqrt2 +(2-4)sqrt3#

Combine the numbers inside the parentheses.

# sqrt2 +(2-4)sqrt3 = sqrt2 -2sqrt3#

#2sqrt3 + sqrt2 - 4sqrt 3 = sqrt2 -2sqrt3#

That's about as simple as you can get it.